Power resources and grassroots activism: Worker organising potentials in logistics centres and online food delivery in Poland - Adam Mrozowicki; Szymon Pilch (Work Organisation, Labour and Globalisation)
In the context of debates about logistics as a critical infrastructure of contemporary capitalism, this article addresses the question of the conditions under which workers’ structural power can be translated into the organisation of collective interests. Based on original empirical research (30 interviews) in online food delivery and logistic centres in Poland, the article argues that ‘organising potential’ is greater in the latter. This finding is explained by the innovative activities of new, radical and grassroots trade union leaders and the availability of ‘societal power resources’, including the presence of Amazon as a global target of union protest (a ‘reverse Amazon effect’) and more developed union solidarity networks.